Tatwīru Wihdati Ta’līmi al-Lugati al-Arabīyah Alā Asāsi al-Qur’āni Li al-atfal Hāfidi al-qur’ān - Abicandra, Muhammad Nidom Hamami; Muqit, Abdul (Faculty of Tarbiyah and Teacher Training, IAIN Jember, 2022)
Public interest in learning Arabic continues to increase, as evidenced by the increasing number of formal and non-formal educational institutions that include Arabic in the curriculum taught to students. The increasing public interest in Arabic aligns with the growing awareness that Arabic is a language. By studying the Arabic language, it is hoped that students will be able to understand the Koran well. However, the amount of public interest differs from providing adequate teaching materials and is far from attractive for children. So learning Arabic seems superficial and far from the needs of students and the expectations of society. The formulation of the problems in this study are (1) What are the components of developing a Koran-based Arabic module for children who memorize the Koran at SDIT Harapan Umat and Rumah Tahfidz al-Kifach Jember, (2) What is the validity of the Koran-based Arabic module for children? Children, who memorize the Koran at SDIT Harapan Umat and Tahfidz al-Kifach Jember House? (3) how effective and attractive is the Arabic language module based on the Koran for children who memorize the Koran at SDIT Harapan Umat and Rumah Tahfidz al-Kifach Jember? The aims of this study were (1) to produce a valid, effective and interesting Koran-based Arabic language learning module for children at Tahfidz al-Kifach House. This type of research is research and development (R&D) by adapting the Borg, and Gall (1983) development model, namely (1) needs analysis, (2) product development, (3) preparation of teaching material prototypes, (4) Trials, (5 ) product revisions, and (6) final results. They collected data using interviews, documentation, questionnaires, and tests. This study results in a